Influence of Facial, Head, and Neck Dimensions on Vocal Acoustic Parameters in Polish Speakers - Pawelec, Łukasz; Słowik, Kamila; Lipowicz, Anna (Archives of Acoustics, 2026)
The relationships between human voice parameters and body dimensions have been previously described, but the connections between voice and face geometry remain poorly researched. This study aims to determine the relationships between face dimensions and acoustic parameters in both sexes and examines 111 adult participants (30 males). Each participant undergoes voice recording, which includes five sustained vowels, along with anthropometric measurements of the neck, head, and face regions. Comparisons between voice parameters and the head, face, and neck regions are conducted employing Pearson’s correlation coefficients (r) and a multiple linear regression model. The results reveal significant relationships between head, neck, face dimensions and acoustic parameters in both sexes. Males with higher noses, greater head circumferences, and wider faces tend to have lower formants and more stable voices. Females with larger head circumferences had lower formant values, and those with greater neck circumferences tend to have more stable voices. Also, females with increased nose height have a lower fourth formant (F4). Moreover, females with wider faces, noses, and jaws tend to have less rough voices (lower jitter) and longer maximum phonation time (MPT). These findings may be useful for scientists and law enforcement authorities in creating algorithms that build face models based on voice signals.